Monitoring physicochemical and sensory attributes during debittering of stoned green olives - Marx, Ítala M. G. (2019)
Associate Laboratory LSRE-LCM -UID/EQU/50020/2019 -funded by national funds through FCT/MCTES (PIDDAC) and by Project UID/BIO/04469/2013–CEB, and strategic project PEst- OE/AGR/UI0690/2014–CIMO all funded by European Regional Development Fund (ERDF) through COMPETE2020 –Programa Operacional Competitividade e Internacionalização (POCI) –and by national funds through FCT–Fundação para a Ciência e a Tecnologia. Ítala M.G. Marx acknowledges Fundação para a Ciência e a Tecnologia (FCT) through FCT PhD reference: (SFRH/BD/137283/2018)